Development of catfish sausages fortified with duck eggs as a potential nutritional intervention product to reduce stunting rates in toddlers - Izah, Nilatul; Usman, Mukhamad Khumaidi; Hidayah, Seventina Nurul; Afifah, Diana Nur; Syauqy, Ahmad (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: Stunting among toddlers is a significant public health issue in Indonesia, with a high prevalence in various regions, including Tegal City. One of the efforts to reduce stunting is through nutritional interventions based on animal protein that is easily available and has high nutritional value.Objective: This study aimed to develop catfish sausage fortified with duck eggs as a local nutrition intervention to improve children's nutritional status.Materials and Methods: The research was an experimental study using a completely randomized design with three formulations (S1 had 1 egg, S2 had 3 eggs, and S3 had 5 eggs), each repeated three times. The formulations adhered to SNI 3820:2024 standard requiring minimum 75% meat content. Parameters analyzed included protein, fat, moisture content, pH, texture, and amino acid profile. Statistical analysis using one-way ANOVA was applied at 5% significance level.Results: Sausages with duck egg fortification had protein content of 14.55-15.62% and fat content of 5.27-9.08%. Sample S2 showed the highest protein (15.62%), optimal texture (hardness 8N, chewiness 4N), and stable pH (6.2) meeting SNI standards. Amino acid analysis revealed significant levels of lysine (1.85%), histidine (1.24%), and leucine (2.95%).Discussion: Duck egg fortification significantly improved nutritional quality. A 50g serving provides 60-70% of daily protein needs for children aged 1-3 years. Essential amino acids play crucial roles: lysine supports bone growth and calcium absorption, histidine aids tissue repair and immune function, while leucine activates mTOR pathway for muscle protein synthesis. Sample S2 demonstrated the most balanced formulation with optimal protein enrichment while maintaining desirable texture and microbiological stability during cold storage.Conclusion: Catfish sausage fortified with duck eggs has potential as an effective local wisdom-based nutritional intervention for stunting reduction in Indonesia.Keywords: Sausage; catfish; duck egg; protein; stunting